Elite Players Invest Additional Time for Making Better Embodied Choices - Hinz, Matthias; Lehmann, Nico; Musculus, Lisa (Frontiers in Psychology, 2022)
Expert athletes are determined to make faster and better decisions, revealed in several simple heuristic studies using verbal reports or micro-movement responses. However, heuristic decision-making experiments that require motor responses, also being considered as embodied-choice experiments, are still underrepresented. Furthermore, it is less understood, how decision time and confidence depend on the type of embodied choices players make. To scrutinize decision-making processes (i.e., decision time, decision confidence), this study investigated the embodied choices of male athletes with different expertise in a close-to-real-life environment. 22 elite (Mage = 17.59 yrs., SD = 3.67) and 22 amateur (Mage = 20.71 yrs., SD = 8.54) team-handball players performed a sport-specific embodied-choice test. Attack sequences (n = 32) were shown to the players, who had to make a choice between four provided options by giving a respective sport-specific motor response. We analyzed the frequencies of specific choices and the best choice, as well as the respective decision time and decision confidence. Elite and amateur players differed in the frequencies of specific choices (i.e. forward/tackling; passive blocking), and elite players made the best choice more often. Slower decision times of elite players were revealed in specific choices and in best choices, confidence of decisions was rated equally high from both player groups. Indications are provided that elite players make better choices rather slower, instead of faster. We suppose this is due to specific sensorimotor interactions and speed-accuracy-tradeoffs in favor for accuracy in elite players. Our findings extend expert decision-making research by using an embodied-choice paradigm, highlighting considerations of decision time and confidence in future experiments.